Revenue Mobilization as an Impetus for Economic Growth in Sub-Saharan Africa: The Influence of Tax Compliance and Informal Sector - Ackom, Enoch Kojo; Ocansey, Evans O. N. D.; Asamoah, Felix Oppong (Archives of Business Research, 2025)
Revenue mobilization is critical for economic growth and sustainable development in Sub-Saharan Africa (SSA). However, weak tax compliance and the large informal sector continue to constrain governments' ability to generate adequate tax revenues. This study examines the relationship between revenue mobilization, tax compliance, and the informal sector, exploring how these factors shape economic growth in SSA. The study aims to: (1) assess the impact of revenue mobilization on economic growth, (2) investigate the influence of tax compliance on revenue mobilization, (3) examine the role of the informal sector in tax collection, and (4) evaluate the interaction between tax compliance and the informal sector in shaping revenue mobilization. A quantitative research approach is employed using panel data from ten SSA countries between 2010 and 2022. The study uses panel regression models, including fixed-effects estimation, to analyze the relationships between revenue mobilization, tax compliance, and economic growth. Descriptive statistics, correlation analysis, stationarity tests, model specification tests, and multicollinearity checks are conducted to ensure the robustness of the results. The results indicate that revenue mobilization has a significant positive impact on economic growth (p = 0.0003), while government expenditure shows a weak negative effect. Tax compliance positively affects revenue mobilization, but its impact is weaker than expected, suggesting the need for enhanced enforcement and taxpayer education. The informal sector, contrary to conventional beliefs, has a positive but complex relationship with revenue mobilization. The interaction between tax compliance and the informal sector reveals that excessive enforcement may drive informal businesses further underground, reducing overall tax collection. Additionally, financial inclusion is found to be a strong enabler of tax compliance and revenue growth. These findings have significant policy implications, emphasizing the need for balanced tax enforcement, digital financial inclusion, and informal sector integration to enhance revenue mobilization. Governments should focus on incentive-driven tax policies, improved transparency, and efficient public expenditure to maximize tax revenues and foster economic growth. From an accounting research perspective, the study highlights the importance of interdisciplinary approaches in taxation, integrating insights from public finance, behavioral economics, and digital taxation.